Lexicographical resources of the style editor: contributions from the Spanish dictionary of Uruguay - Lucián, Eliana (2019)
This article reflects on lexicographic resources as a tool for style correction. It starts from the importance of knowing the parameters of enunciation when correcting to opt for the linguistic and lexicographical consultation instruments that best suit the variety of Spanish with which a style corrector is working. Then, the Dictionary of the Spanish of Uruguay (deu) is characterized in its role as a frame of reference for the Uruguayan Spanish variety. Subsequently, from concrete textual examples extracted from the national literary and journalistic medium, situations of correction are analyzed. This work concludes that the deu legitimizes certain terms of the Uruguayan Spanish variety and omits others or is ambiguous in its formulation.